2021
DOI: 10.1007/s00590-021-02957-7
|View full text |Cite
|
Sign up to set email alerts
|

The risks associated with tourniquet use in lower limb trauma surgery: a systematic review and meta-analysis

Abstract: Purpose Tourniquet use in lower limb fracture surgery may reduce intra-operative bleeding, improve surgical field of view and reduce length of procedure. However, tourniquets may result in pain and the production of harmful metabolites cause complications or affect functional outcomes. This systematic review aimed to compare outcomes following lower limb fracture surgery performed with or without tourniquet. Methods We searched databases for RCTs comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…In concordance, a recent Cochrane systematic review found tourniquet use to be associated with significantly higher risk of developing wound infection (RR 2.72, 95% CI 1.15 to 6.42); however this study did not employ separate subgroup analyses of superficial and deep infections [ 14 ]. Moreover, an increased incidence of serious adverse events with tourniquet use has also been suggested by other studies in total knee arthroplasty and lower limb trauma surgery [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 70%
“…In concordance, a recent Cochrane systematic review found tourniquet use to be associated with significantly higher risk of developing wound infection (RR 2.72, 95% CI 1.15 to 6.42); however this study did not employ separate subgroup analyses of superficial and deep infections [ 14 ]. Moreover, an increased incidence of serious adverse events with tourniquet use has also been suggested by other studies in total knee arthroplasty and lower limb trauma surgery [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 70%
“…These findings are consistent with recently published meta-analyses on TKA and orthopaedic trauma which have shown significantly reduced operating times when using a tourniquet. 17,18 The shorter operating time is likely to be due to better visualization of the surgical field and less time spent achieving haemostasis. Given the invasive nature and complexity of endoprosthetic reconstructions, the reduction in operating time is proportionately greater in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The existing evidence on tourniquet use in lower limb fracture fixation surgery in adults suggest that using a tourniquet may cause patients harm with limited benefit ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%